Ženske v pravu: "Vrata se bodo najhitreje odprla tistim, ki si jih bodo drznile odpreti same" - Mele, Kaja (Pravnik, 2025)
The article examines the dilemma frontline emergency officials face in balancing strict adherence to rules with the need for discretion in crisis situations. Focusing on "infra-law" - a set of informal, flexible regulations specific to street-level bureaucracy - the author proposes that infra-law can moderate the discretion exercised by these officials. Given that emergencies are inherently unpredictable and urgent, he argues that strict rule-following often fails, making discretion necessary for effective crisis response. However, excessive discretion risks inconsistency and arbitrariness, undermining legality and public trust. Infralaw, typically embodied in directives, protocols, or internal guidelines, offers a middle ground. By providing a real-time guidance adaptable to the unique demands of specific emergencies, infra-law helps align frontline actions with overarching legal and organisational frameworks while respecting the practical realities of emergency decision-making. This framework, supported by organisational disciplinary power, aims to limit arbitrariness and maintain legality, ensuring that emergency responses remain both flexible and accountable.